PENINGKATAN KEMAMPUAN MEMBACA MELALUI PERMAINAN KARTU HURUF PADA SISWA KELAS I SD NEGERI 05 SIALANG KECAMATAN KAPUR IX KABUPATEN LIMA PULUH KOTA - Jusnilai, Jusnilai (Ensiklopedia Education Review, 2019)
Based on observations made in class I of Sialang 05 Elementary School, Kapur IX District, Lima Puluh Kota Regency, it appears that the reading ability of class I students is low. This study aims to improve reading skills through the first class Letters Card game of Sialang 05 Elementary School, Kapur IX District, Lima Puluh Kota Regency. This research is a classroom action research with stages of planning, implementation, observation, and reflection. This research was conducted in 2 cycles. Data collection methods used in this study are observation and performance methods. The collected data is then analyzed descriptively quantitatively. The results of the study showed that through letter card games able to improve the reading ability of Grade 1 students at SD Negeri 05 Sialang sub-district of Limestone IX District of Lima Puluh Kota. Therefore the use of letter cards in learning in class I needs to be improved, especially in an effort to improve reading skills.